Quantifying Light Dilution in Ultraviolet Spectroscopic Measurements of Volcanic SO2 Using Dual-Band Modeling - Varnam, Matthew; Burton, Mike; Esse, Ben; Kazahaya, Ryunosuke; Salerno, Giuseppe; Caltabiano, Tommaso; Ibarra, Martha (Frontiers in Earth Science, 2020)
High precision and accuracy in volcanic SO2 emission rate quantification is critical for eruption forecasting and, in combination with in-plume gas ratios, quantifying global volcanic emission inventories. Light dilution, where scattering of ultraviolet light dilutes plume SO2 absorbance signals, has been recognized for more than 50 years, but is still not routinely corrected for during gas flux quantification. Here we use modeling and empirical observations from Masaya volcano, Nicaragua, to show that light dilution produces: i) underestimates in SO2 that can reach a factor of 5 and, at low column densities, cause little impact on standard retrieval fit quality, even for heavily diluted spectra; ii) retrieved SO2 amounts that are capped by a maximum value regardless of the true amount of SO2, with this maximum amount being reduced as light dilution increases. Global volcanic volatile emission rates may therefore be significantly underestimated. An easily implementable dual-waveband analysis provides a means to detect, and in clear sky conditions, correct dilution effects directly from the spectra, opening a path to more accurate SO2 quantifications.